EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KOPI ROBUSTA (Coffea canephora L.) DI NAGARI LUBUK KARAK KECAMATAN SEMBILAN KOTO KABUPATEN DHARMASRAYA - khoriyah, Zulfebri; Edwin, GE; Rezki, Dewi (Rawa Sains: Jurnal Sains STIPER Amuntai, 2023)
Nagari Lubuk Karak has the potential for the development of robusta coffee plants, therefore it is necessary to evaluate the suitability of the land in the area. This study aims to determine the land suitability class for robusta coffee plants, and obtain maps of actual and potential land suitability for robusta coffee plants. The research method used in this study is a survey method. The stages in the research include secondary data collection, pre-survey, primary survey and soil analysis in the laboratory. Land suitability classification is done by matching method. From the results of the study, it is known that the actual land suitability of land units (SL) 1, 8, 9, 10, 11 is S3nr, which is marginal according to the limiting factor of nutrient retention, SL 2 and 3 are S3nr,eh, which is marginal according to the limiting factor of nutrient retention and erosion hazard, SL 4, 5, 6, 7 is Neh which is not in accordance with the limiting factor of erosion hazard. Meanwhile, the potential land suitability in SL 1 is S2wa,nr which is quite in accordance with the limiting factors of water availability and nutrient retention, SL 2 and 3 are S2tc,wa,nr,eh,lp which is quite in accordance with the limiting factors of temperature, water availability, retention nutrient, erosion hazard and land preparation, SL 4, 5, 6, 7 is Neh which is not in accordance with the limiting factor of erosion hazard, SL 8 is S2tc,wa,nr which is quite in accordance with the limiting factor of temperature, water availability and nutrient retention, SL 9, 10, 11 are S2tc,wa,nr,eh which is quite suitable for the limiting factors of temperature, water availability, nutrient retention and erosion hazard. To obtain optimal land quality for Robusta coffee plants, improvements can be made based on the limiting factors in each land unit.